Effects of Energy Drink Types on Male and Female Drivers in an Effort to Reduce Drowsiness While Driving - Jovan Kurnia, Christopher; Siswanto, Daniel; Susanto, Sani (Ann Publisher, 2024)
Energy drinks are stimulants that men or women generally use to handle sleepiness while driving with sleep deprivation. There is no study about energy drink’s effect on gender. This study aims to learn about energy drinks in different genders while driving with sleep deprivation. Research is done using a laboratory approach using a driving simulator. Ten men and ten women were participants (21 ± 0.95 years). Participants were asked to drive for 90 minutes, and before driving the simulator, participants drank coconut water or Kratingdeng based on the planned order. PVT measured awareness before and after participants used the simulator. Dependent variables measured are mean RT, %minor lapses, and mean 1/RT. EEG evaluated sleepiness during the driving session. Based on ANOVA, energy drinks did not influence mean RT (p-value = 0,088), mean 1/RT (p-value= 0,058), %minor lapses (p-value =0,571), and EEG (p-value = 0,348). Meanwhile, EEG measured sleepiness and was only influenced by gender (p-value = 0,048). Based on the test, there is no difference between the two energy drinks. It is caused by an energy drink’s material that gives the body the same stimulant level. There is a difference in Mean 1/RT between gender and energy drinks. It is caused by composition such as potassium in coconut water or taurine and caffeine in Kratingdeng. The research shows that energy drinks do not influence awareness and sleepiness while driving for 90 minutes. However, energy drinks give different results in awareness of different genders.